Nano-mediated strategy for targeting and treatment of non-small cell lung cancer (NSCLC) - Ashique, Sumel; Garg, Ashish; Mishra, Neeraj; Raina, Neha; Long, Chiau Ming *; Tulli, Hardeep Singh; Behl, Tapan; Rani, Radha; Gupta, Madhu (Springer, 2023)
Lung cancer is the most common type of cancer, with over 2.1 million cases diagnosed annually worldwide. It has a high incidence and mortality rate, leading to extensive research into various treatment options, including the use of nanomaterial-based carriers for drug delivery. With regard to cancer treatment, the distinct biological and physico-chemical features of nano-structures have acquired considerable impetus as drug delivery system (DDS) for delivering medication combinations or combining diagnostics and targeted therapy. This review focuses on the use of nanomedicine-based drug delivery systems in the treatment of lung cancer, including the use of lipid, polymer, and carbon-based nanomaterials for traditional therapies such as chemotherapy, radiotherapy, and phototherapy. The review also discusses the potential of stimuli-responsive nanomaterials for drug delivery in lung cancer, and the limitations and opportunities for improving the design of nano-based materials for the treatment of non-small cell lung cancer (NSCLC).